Developing Writing Identity in an Advanced Agricultural Communications Media Writing Course - Holli R. Leggette; Holly Jarvis; David Walther (Journal of Applied Communications, 2015)
Writing is a complex process students use to interpret assumptions, make meaning, solidify intentions, and convey knowledge. The purpose of this study was to use Chickering and Reisser’s (1993) theory of education and identity to understand students’ perspectives on how their experience in an advanced agricultural communications media writing course helped them develop their identity as writers. At the end of the course, 57 students completed one-page reflections that were analyzed using content analytic induction (Patton, 2002) guided by Chickering and Reisser’s (1993) seven vectors of college student development. Students showed evidence of experiencing growth in each vector and became media writers who could identify themselves as writers even if they did not intend to pursue a writing career. Student-faculty relationships were key factors in writing identity development because students valued the instructor feedback and human connection. The second major assignment was the point at which they either identified themselves as writers or they did not. Perhaps this was because students were immersed in a structured writing process during that time. Students indicated the value is not in the word but in the author’s ability to connect words into a cohesive structure that captures an audience. Based on this study, agricultural communications instructors should focus on teaching students the pathway to the end product and not focus on teaching the end product. More research, therefore, needs to be conducted on what components of the second major writing assignment helped students become more effective writers and helped them develop identity as writers.
Keywords: Advanced media writing; writing-intensive course; education and identity